Clinical Profile, Complications, Management, and Outcome of Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis: A North Indian Study - Habib, Mudasir; Dar, Hilal Ahmad; Khan, Mushtaq Ahmad; Shah, Altaf Hussain; Zargar, Showkat Ali; Singh, Bhagat; Sheikh, Nadeem Ahmad; Ashraf, Aadil; Mohammad, Sozia (Journal of Digestive Endoscopy, 2018)
Aim: The aim of this study was to assess clinical profile, complications, management, and outcome of postendoscopic retrograde cholangiopancreatography (ERCP) pancreatitis. Methods: In this prospective study, 1320 patients were followed for the development of post‑ERCP pancreatitis. Post‑ERCP complications and outcome were assessed. Results: The percentage of post‑ERCP pancreatitis in our patients was 5.3%. The mean age of patients with post‑ERCP pancreatitis was 49.9 years. About 15.7% of the patients who developed post‑ERCP pancreatitis experienced complications in the form of respiratory failure and sepsis. Conclusion: The incidence of post‑ERCP pancreatitis was 5.3%. The major complications after post‑ERCP pancreatitis were respiratory failure and sepsis. The outcome of post‑ERCP pancreatitis was good, as there was no mortality. However, majority of patients with severe post‑ERCP pancreatitis developed sepsis and received antibiotics.
Keywords: Endoscopic retrograde cholangiopancreatography; hyperamylasemia; pancreatitis; respiratory failure; sepsis